The relationship between social determinants of health and girls' age at menarche based on the world health organization model: path analysis. Issue 10 (October 2022) - Nasiri, Saeideh; Dolatian, Mahrokh; Ramezani Tehrani, Fahimeh; Alavi Majd, Hamid; Bagheri, Azam
Abstract: Objectives: Given the descending trend of menarche age and the effect of social determinants of health on menarche, the present study was conducted to examine the relationship model of social determinants of health with menarche age of girls. Materials and methods: The present cross-sectional study enrolled 840 mothers and their 6-17 year-old daughters in the city of Kashan, Iran (2020). Questionnaires used included: demographic-family questionnaire for mothers and daughters, question about age at menarche, Perceived Social Support, Physical Activity, Socioeconomic Status, Spiritual Health, General Health Questionnaire, the quality of couple's relationship and the family communication pattern. The statistical analysis was performed in SPSS-16, and the relationship model was examined using path analysis method in LISREL-8.8. Results: The girls' menarche age was directly affected by sister's (b = 0.83) and mother's menarche age (b = 0.05), BMI (b = 0.01), physical activity (b = -0.06), conversation orientation (b = -0.002), socioeconomic status (b = -0.01) and maternal general health (b = 0.009). It was also indirectly affected by mother's menarche age, social support, socioeconomic status, and maternal spiritual health and parents relationships. Conclusions: The results showed that the numerous factors affect the girls' age at menarche directly and indirectly. Considering mutual interaction of factors revealed in the proposed model, it is recommended this model be used as an appropriate framework in research, design and implementation of programs relating to adolescent girls. Abstract : Menarche; Puberty; Menstruation; Social determinants of health.